Effects of tension wood on specific conductivity and vulnerability to embolism of Quercus ilex seedlings grown at two atmospheric CO2 concentrations - Gartner, Barbara L; Roy, Jacques; Huc, Roland (Tree Physiology, 2003)
To determine whether there are decreases in hydraulic function of a woody stem when it has increased mechanical loading, Quercus ilex L. seedlings were grown upright or inclined to force the production of large amounts of tension wood (TW). Seedlings were grown in ambient or elevated carbon dioxide concentrations ([CO2]) for 16–17 months to provide two sets of seedlings differing in growth rates and allocation patterns. In both CO2 environments, inclination caused formation of large amounts of TW at the base and mid-section of most stems, but not at the stem tips. Contrary to expectation, there were no significant effects of stem inclination or amount of TW on specific conductivity (ks) or vulnerability to embolism. Samples with high amounts of TW had higher vessel frequency, similar average vessel lumen area, similar vessel lumen fraction (6% of the transverse area), elevated frequency of vessels in the smallest diameter class, and higher wood density than samples with very little TW. Samples from seedlings in the elevated [CO2] treatment had similar vessel frequency, larger average vessel lumen area (caused by a higher frequency of large-diameter vessels), similar vessel lumen fraction, and similar wood density as samples from seedlings in the ambient [CO2] treatment. There was a strong position effect: the highest wood density and lowest ks were at the stem base, intermediate values were at the middle, and the lowest density and highest ks were at the stem tip. We conclude that, in a species that uses different cells for mechanical support and water transport, there can be large modifications in performance of the mechanical function through TW formation without impacting the water transport functions—ks and vulnerability to embolism.
10.1093/treephys/23.6.387
Keywords: ecological wood anatomy; evergreen; hydraulic architecture; Mediterranean; structure/function relationship

Effects of tension wood on specific conductivity and vulnerability to embolism of Quercus ilex seedlings grown at two atmospheric CO2 concentrations - Gartner, Barbara L.; Roy, Jacques; Huc, Roland (Tree Physiology, 2003)
To determine whether there are decreases in hydraulic function of a woody stem when it has increased mechanical loading, Quercus ilex L. seedlings were grown upright or inclined to force the production of large amounts of tension wood (TW). Seedlings were grown in ambient or elevated carbon dioxide concentrations ([CO2]) for 16–17 months to provide two sets of seedlings differing in growth rates and allocation patterns. In both CO2 environments, inclination caused formation of large amounts of TW at the base and mid-section of most stems, but not at the stem tips. Contrary to expectation, there were no significant effects of stem inclination or amount of TW on specific conductivity (ks) or vulnerability to embolism. Samples with high amounts of TW had higher vessel frequency, similar average vessel lumen area, similar vessel lumen fraction (6% of the transverse area), elevated frequency of vessels in the smallest diameter class, and higher wood density than samples with very little TW. Samples from seedlings in the elevated [CO2] treatment had similar vessel frequency, larger average vessel lumen area (caused by a higher frequency of large-diameter vessels), similar vessel lumen fraction, and similar wood density as samples from seedlings in the ambient [CO2] treatment. There was a strong position effect: the highest wood density and lowest ks were at the stem base, intermediate values were at the middle, and the lowest density and highest ks were at the stem tip. We conclude that, in a species that uses different cells for mechanical support and water transport, there can be large modifications in performance of the mechanical function through TW formation without impacting the water transport functions—ks and vulnerability to embolism.
10.1093/treephys/23.6.38710.1093/treephys/23.6.387
Keywords: ecological wood anatomy; evergreen; hydraulic architecture; Mediterranean; structure/function relationship